Prevalence and Antibiotic Susceptibility Profile of Methicillin-Resistant Staphylococcus aureus (MRSA) Isolates in Diabetes Patients with Foot Ulcers - Unegbu Valentine N; Nwachukwu Ndubuisi O; Obum-Nnadi Charity N; Okey-ndeche Ngozika F (Journal of Medical Microbiology and Infectious Diseases)
Introduction: methicillin-resistant Staphylococcus aureus (MRSA) infection is common among diabetes patients with foot ulcers. This study aimed to determine MRSA isolates prevalence and antibiotic susceptibility profile in diabetic foot ulcers (DFU) patients. Methods: A total of 204 patients with diabetic foot ulcers admitted to a tertiary hospital in Abia State, Nigeria, were included in the assay. Specimens were obtained by scraping the ulcer base or the deep portion of the wound edge using a sterile curette and were promptly sent to the laboratory for culture, identification, and antibiotic susceptibility test.  Results: The MRSA prevalence in DFU patients was 22.1% (n=45). Male patients with DFU were more infected with MRSA (n= 26, 12.7%) than females (n=19, 9.3 %), but the difference was not statistically significant (P < 0.14). The age group 41-60 years had the highest prevalence (n=27, 13.2%), statistically significant (P < 0.02). Farmers had the highest prevalence of 9.8% (n=20) while the least (0.5%) was seen in housewives (n=1) with no statistical significance (P < 0.07). The antibiotics sensitivity pattern of MRSA showed 100% sensitivity to vancomycin and chloramphenicol but 100% resistance to penicillin, ceftriaxone, and oxacillin. The multidrug-resistant index was all > 0.2. Conclusions: The prevalence of MRSA in DFU patients in a tertiary hospital in Abia State was very high, with an alarming rate of drug-resistant bacteria due to the possibility of misuse and abuse of antibiotics among the populace, which requires collaborations from all stakeholders to prevent drug resistance in the study settings.